2017
DOI: 10.33546/bnj.77
|View full text |Cite
|
Sign up to set email alerts
|

The Development of E-Partograph Module as a Learning Platform for Midwifery Students: The Addie Model

Abstract: To enhance the competencies of midwifery students, one must design the learning instruction in such a manner that it will optimize learning. The learning materials designed based on technology will facilitate the learners to achieve the desired outcome. In this study, e-partograph was developed using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instruction model. While the module of E-partograph was followed the structural guideline of Department of National Education of Indonesia cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…Roh, Lee, and Mennenga () indicated that although health professions’ education has seen an increase in the use of new pedagogical methodologies recently, few studies of such methodologies have reflected a positive educational outcome. As an appropriate instructional design is required to ensure meaningful learning (Morrison, ), the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, which has been considered essential in the development and evaluation of educational programs (Hadi et al , ; Muruganantham, ), was adopted. This model has been recognized as effective, attractive, and efficient in delivering educational content in many disciplines (Lu, Cheng, & Chan, ; Morrison, ).…”
Section: Introductionmentioning
confidence: 99%
“…Roh, Lee, and Mennenga () indicated that although health professions’ education has seen an increase in the use of new pedagogical methodologies recently, few studies of such methodologies have reflected a positive educational outcome. As an appropriate instructional design is required to ensure meaningful learning (Morrison, ), the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, which has been considered essential in the development and evaluation of educational programs (Hadi et al , ; Muruganantham, ), was adopted. This model has been recognized as effective, attractive, and efficient in delivering educational content in many disciplines (Lu, Cheng, & Chan, ; Morrison, ).…”
Section: Introductionmentioning
confidence: 99%
“…28 Instructional System Design (ISD) per se is a systematic methodology used for the development of education and training programs with the aim of improving student abilities. 24 One of the advantages of using the ADDIE model is that it can be easily applied to curricula that teach theoretical knowledge, practical skills, and ethics. 29 Several previous studies have also used 24 in developing an e-partograph module for midwifery students.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The knowledge and skills of midwifery students saw an increase since the use of technology in learning. 23,24 Using e-learningbased media that are different, unique, and well-prepared can support the development of skills, knowledge, and behavior of nursing students. 25 It can thus be concluded that learning using e-learning-based media can improve students' knowledge, skills, and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the assessment of the suitability of the developed process, presented in three dimensions (in an overview, by components, and in terms of authentic use) is at the highest level. This implies that the application of the ADDIE model (Hadi et al, 2017), instructional design, and system approach (Montre, 2018) with the emphasis on the learners' participation in problem-based analysis thinking activities, the analysis thinking and learning achievement are increased. This is in compliance with Amornkitpinyo and Piriyasurawong's research (2017) on two-stage methodologies: 1) the first stage is to synthesize the concept of the framework of the structural equation model of mobile cloud learning acceptance for higher education students in the 21st century, and 2) the second stage proposes the design structural equation model of mobile cloud learning acceptance for higher education students in the 21st century.…”
Section: Conclusion and Discussionmentioning
confidence: 99%